2018
DOI: 10.1098/rsos.181168
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scale changes the relationship between beta diversity, species richness and latitude

Abstract: The relationship between β-diversity and latitude still remains to be a core question in ecology because of the lack of consensus between studies. One hypothesis for the lack of consensus between studies is that spatial scale changes the relationship between latitude and β-diversity. Here, we test this hypothesis using tree data from 15 large-scale forest plots (greater than or equal to 15 ha, diameter at breast height ≥ 1 cm) across a latitudinal gradient (3–30o) in the Asia-Pacific region. We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 40 publications
3
40
1
Order By: Relevance
“…We note that our findings of low cross-taxon congruence apply to the 0.25-ha scale at which we sampled, which is typical for biodiversity survey in Australia (Woinarski et al 2002, Kutt and Woinarski 2007, Eyre 2012) and elsewhere in the world (Brown and Heske 1990, Tietje et al 1991, Hanya 2005, Sreekar et al 2018. Cross-taxon congruence might be expected to be higher if assessed at larger spatial scales (Dumbrell et al 2008, Westgate et al 2014, especially if such scales over-ride the finer-scale patterning typically shown by invertebrates (Ferrier et al 1999, French 1999, Pik et al 2002.…”
Section: Discussionmentioning
confidence: 56%
“…We note that our findings of low cross-taxon congruence apply to the 0.25-ha scale at which we sampled, which is typical for biodiversity survey in Australia (Woinarski et al 2002, Kutt and Woinarski 2007, Eyre 2012) and elsewhere in the world (Brown and Heske 1990, Tietje et al 1991, Hanya 2005, Sreekar et al 2018. Cross-taxon congruence might be expected to be higher if assessed at larger spatial scales (Dumbrell et al 2008, Westgate et al 2014, especially if such scales over-ride the finer-scale patterning typically shown by invertebrates (Ferrier et al 1999, French 1999, Pik et al 2002.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, our first hypothesis is that species beta diversity of understory V. uliginosum communities in broadleaf forests is higher than that in coniferous forests, and the pattern is consistent at different latitudes. In previous studies, the scale dependence of beta diversity was frequently reported [11,23]. Thus, our second hypothesis is that species beta diversity of different forest types and latitudes is distinct at different spatial scales.…”
Section: Introductionmentioning
confidence: 79%
“…On the other hand, the impacts of biotic or abiotic factors on beta diversity probably depend on scales. For example, Sreekar et al [23] found contrasting effects of latitude on tree beta diversity at small and large spatial scales, and Martin and Wilsey [11] found that the differences in beta diversity between grassland types changed across spatial scales. Therefore, it seems that the influences of forest types and/or latitude on species beta diversity may vary with scales, which, however, has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…That is, local biodiversity increases at a decelerating rate with increasing spatial scale (e.g., the species-area relationship), and therefore many patterns of biodiversity depend critically on scale (e.g., Rahbek 2005; Harrison et al 2006;Chase et al, 2018). As a result of the growing awareness of the importance of spatial scale in biodiversity measurements and interpretations of possible mechanisms, there has been a steady increase in interest in measuring and comparing spatial beta-diversity (Anderson et al 2011;De Cáceres et al 2012, Sreekar et al, 2018Xing & He 2019). Beta-diversity, as first defined by Whittaker (1960Whittaker ( , 1972, offers a mathematical link between local (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, null distributions can be generated maintaining alpha diversity, gamma diversity, abundance structures and/or numbers of individuals (Mori, Fujii, Kitagawa & Koide, 2015;Qian, Wang & Zhang, 2012;Kraft et al, 2012;Brocklehurst, Day & Fröbisch, 2018). Although there is an emerging consensus that abundance-based null models are superior to incidence-based ones (Tucker et al, 2016), these approaches have been criticized because they ignore the completeness of the samples (Ulrich et al 2017, Sreekar et al 2018).…”
Section: Introductionmentioning
confidence: 99%